Performance of Electrocoagulation Process for Removal of Sulphate Ion from Aqueous Environments Using Plate Aluminum Electrodes - a.h Mahvi (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2012)
Background and Objectives: Sulphate ion is one of the main ions available in natural and waste water. The high rate of sulphate in drinking water causes health problems such as irritation and digestive problems and makes water taste bitter. The purpose of this study was to assess the efficiency of sulphate ion removal from drinking water through Electrocogualation process (EC) using plate aluminum electrodes. Methods: This study was conducted as a pilot plant using one glass tank in the volume of 1.3liter containing 6 plate aluminum electrodes. These electrodes were attached to a power supply in a mono-polar and parallel arrangement in order to switch the alternating current to the direct one. That is, each electrode was attached to positive and negative poles directly and alternately. The tank was filled with synthetic water containing sulphate ion with the concentration of 350 & 700mg/L. Percentage of sulphate ion removal in potential range of 10, 20 and 30 V, reaction times of 40, 20 and 60min and pH 7.0, 3.0 & 11.0 were measured. Results: In this study the maximum efficiency of sulphate ion removal was in the electrical potential of 30 V, reaction time of 60min and pH 11.0. With increase of ion concentration, the time needed to achieve a suitable efficiency of removal increased, that is, it indicated the direct effect of pH and difference of electrical potential on removal of sulphate ion through EC process. Conclusion: The results of this research show that Electrocogualation technology can be introduced as a suitable and promising technique to remove sulphate ion from aqueous environments using plate aluminum electrodes.